Measurement of nasal and fractional exhaled nitric oxide in children with upper airway inflammatory disease: Preliminary results. Issue 12 (December 2015) - Liu, Dabo; Huang, Zhenyun; Huang, Yaping; Yi, Xinhua; Chen, Xi
Abstract: Objectives: To assess the clinical significance of nasal nitric oxide (nNO) and fractional exhaled nitric oxide (FeNO) concentrations in children with upper airway inflammatory disease. Methods: Fifteen healthy children, 30 with allergic rhinitis (AR), 10 with non-allergic rhinitis (NAR), and 30 with sleep disordered breathing (SDB) were enrolled. The FeNO and nNO concentrations were measured non-invasively using a NIOX MINO system. Results: Both nNO and FeNO were significantly higher in children with AR than in healthy children ( P = 0.000 and P = 0.000, respectively). Compared to healthy children, nNO was also significant higher in children with NAR ( P = 0.011) or SDB ( P = 0.027). In contrast, FeNO did not differ from controls in children with NAR or SDB. Conclusions: Our data suggest that nNO has potential value for diagnosing upper airway inflammation. Moreover, elevated FeNO distinguishes allergic from non-allergic rhinitis.